2010
DOI: 10.1007/s11270-010-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Rapid Loss of Endocrine Disruptors from Wetlands Used to Store Either Tertiary Treated Sewage Effluent or Stormwater Runoff

Abstract: The disruption of endocrine systems due to environmental contaminants potentially impacts on the developmental, behavioural, regulatory and reproductive systems of animals. A major source of exposure of animals (terrestrial and aquatic) to endocrine-disrupting compounds is through contact with contaminated surface waters contaminated with sewage effluent and/or stormwater discharge. We studied the response to endocrine-disrupting compounds of Gambusia holbrooki mosquito fish resident of wetlands that were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Over time, metals that are below the limit of detection in flowing waters can accumulate to measurable concentrations within wetlands (especially in the sediments) but there may not always be a clear trend between concentration and distance from the inlet (Calijuri et al, 2011). Movement of water through a sequence of wetlands has been shown to result in a gradual reduction in biomarker response associated with the presence of endocrine-disrupting compounds (Norris and Burgin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, metals that are below the limit of detection in flowing waters can accumulate to measurable concentrations within wetlands (especially in the sediments) but there may not always be a clear trend between concentration and distance from the inlet (Calijuri et al, 2011). Movement of water through a sequence of wetlands has been shown to result in a gradual reduction in biomarker response associated with the presence of endocrine-disrupting compounds (Norris and Burgin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, estrogens like ethinylestradiol in sewage effluents have been linked to extensive harm to fish populations, including damage to their breeding capabilities [102]. observed consistent differences in adult fish length, suggesting an endocrine disruption effect from treated sewage effluent [103]. progestogens, androgens, estrogens, and phenols in sewage treatment plant effluent near Dianchi Lake in China [104].…”
Section: Impacts On Aquatic Faunamentioning
confidence: 99%
“…For example, Donnelly et al [72] reported that sewage effluent discharged into a shallow oligotrophic 'billabong' (approximately 1.6 m in depth) initially resulted in nitrification, and this was followed in succession by collapse of the wetland's macrophyte communities and ultimately increased prevalence of algal blooms over approximately a 15-year period. Such anthropogenic changes typically have a substantial impact on aquatic fauna [73,74], which may be exacerbated when endocrine disrupting compounds are released in human effluent [75][76][77], even with tertiary treatment [78,79].…”
Section: Impacts Of Effluent Dischargementioning
confidence: 99%